2000
DOI: 10.1097/00006123-200008000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anatomic and Neurophysiological Methods for Subthalamic Nucleus Targeting

Abstract: Although all anatomic targeting methods provide accurate STN localization, a combination of the three methods offers the best correlation with the final physiological target. In our experience, direct magnetic resonance targeting was the least accurate method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
115
2
28

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 45 publications
4
115
2
28
Order By: Relevance
“…Past studies comparing 3D mapping of the target and direct MR guided planning showed an inferior accuracy of MR guided planning (6). The progress in MR imaging, better protocols with a superior resolution, and elimination of distortion results in more centres inclining to MR guided planning, sometimes without a microelectrode recording and using one track (7,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies comparing 3D mapping of the target and direct MR guided planning showed an inferior accuracy of MR guided planning (6). The progress in MR imaging, better protocols with a superior resolution, and elimination of distortion results in more centres inclining to MR guided planning, sometimes without a microelectrode recording and using one track (7,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Bejjani et al reported that MRI alone was not sufficient in their experience of 12 cases in which T2-weighted coronal images were used for targeting 1) . Zonenshayn and colleagues found that MRI targeting was the least accurate method with an average error of 2.6 mm 38) . Our experience supports their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups provided data showing image distortion and low resolution may make direct targeting using T2WI alone problematic. 2,59 Others have shown good clinical results using this sequence while scanning a patient who is anesthetized and undergoing direct anatomical surgical techniques. 38 Distortion remains one of the most significant challenges in MRI imaging of the STN.…”
Section: Spin Echo Techniquesmentioning
confidence: 98%
“…MRI distortion alone in T2 fast SE (FSE) sequences has been shown to cause a total error of up to 2.4 mm, limiting the accuracy of MRI in targeting very small structures. 59 These distortions have been noticed particularly at the peripheries of the target structures, obscuring tissue borders. 34 This distortion appears to be amplified when using T2 FSE sequences in combination with a stereotactic head frame; however, more recent studies have suggested that this distortion may not be as significant as hypothesized.…”
Section: Spin Echo Techniquesmentioning
confidence: 99%